FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSKLUSIF DI PUSKESMAS BUHIT SAMOSIR TAHUN 2023 - Seriyana Sijabat; Mindo Tua Siagian; Seri Asnawati Munthe; Donal Nababan; Mido Ester J. Sitorus (Universitas Pahlawan, 2023)
Breast milk is the ideal nutrition for babies which contains nutrients that are best suited to the needs of babies as well as protective substances to fight disease. The success of exclusive breastfeeding is influenced by many factors. The aim of the research is to find out the factors related to exclusive breastfeeding at Buhit Samosir Health Center in 2023. Quantitative research method with a cross sectional approach. The research was carried out at the Buhit Samosir Health Center in November 2022-July 2023. The study population was 30 people, the total sampling technique was 30 people. Bivariate analysis of chi-square test and multivariate multiple logistic regression test. The results of the study showed that 10 people (33.3%) who gave exclusive breastfeeding were mostly 25-35 years old and 17 people (56.7%) who did not exclusively breastfeed were 25-35 years old. The majority of breastfeeding mothers have good knowledge (score 23-30) of 24 people (80%), the majority of mothers who give exclusive breastfeeding have good knowledge (score 23-30) of 8 people (26.7%) and the majority of mothers who do not give exclusive breastfeeding good knowledge (score 23-30) as many as 16 people (53.3%). The majority of breastfeeding mothers have a fairly good attitude (score 49-55) as many as 15 people (50%), the majority of mothers who give exclusive breastfeeding have a good attitude (score 56-75) as many as 5 people (16.7%) and the majority of mothers who do not exclusively breastfeed attitude is quite good (score 49-55) as many as 12 people (40%). The majority of breastfeeding mothers had no history of illness as many as 22 people (73.3%), the majority of mothers who gave exclusive breastfeeding had no history of illness as many as 11 people (36.7%) and mothers who were not exclusively breastfed the majority had no history of disease as many as 11 people ( 36.7%). The majority of breastfeeding mothers with first parity gave birth or parity > 4 as many as 18 people (60%), the majority of mothers who gave exclusive breastfeeding with first parity gave birth or parity > 4 as many as 7 people (23.3%) and mothers who were not exclusively breastfed the majority with first parity gave birth or parity> 4 as many as 11 people (36.7%). The dominant factor in exclusive breastfeeding is the attitude factor with a significance value of 0.001 <0.005. Keywords: Exclusive breastfeeding, age, knowledge, attitudes, medical history, parity